Genome sequence of the filamentous soil fungus Chaetomium cochliodes reveals abundance of genes for heme enzymes from all peroxidase and catalase superfamilies. (December 2016) - Zámocký, Marcel; Tafer, Hakim; Chovanová, Katarína; Lopandic, Ksenija; Kamlárová, Anna; Obinger, Christian
Abstract Background The ascomycetous familyChaetomiaceae (class Sordariomycetes) includes numerous soilborn, saprophytic, endophytic and pathogenic fungi which can adapt to various growth conditions and living niches by providing a broad armory of oxidative and antioxidant enzymes. Results We release the 34.7 Mbp draft genome ofChaetomium cochliodes CCM F-232 consisting of 6036 contigs with an average size of 5756 bp and reconstructed its phylogeny. We show that this filamentous fungus is closely related but not identical toChaetomium globosum andChaetomium elatum . We screened and critically analysed this genome for open reading frames coding for essential antioxidant enzymes. It is demonstrated that the genome ofC. cochliodes contains genes encoding putative enzymes from all four known heme peroxidase superfamilies including bifunctional catalase-peroxidase (KatG), cytochromec peroxidase (CcP), manganese peroxidase, two paralogs of hybrid B peroxidases (HyBpox), cyclooxygenase, linoleate diol synthase, dye-decolorizing peroxidase (DyP) of type B and three paralogs of heme thiolate peroxidases. Both KatG and DyP-type B are shown to be introduced into ascomycetes genomes by horizontal gene transfer from various bacteria. In addition, two putative large subunit secretory and two small-subunit typical catalases are found inC. cochliodes . We support our genomic findings with quantitative transcription analysis of nine peroxidase & catalase genes. Conclusions We delineate molecular phylogeny of five distinct gene superfamilies coding for essential heme oxidoreductases inChaetomia and from the transcription analysis the role of this antioxidant enzymatic armory for the survival of a peculiar soil ascomycete in various harsh environments.